QoS routing for multiple additive QoS parameters using genetic algorithm - Yussof S.; See O.H. (2023)
This paper presents an algorithm for QoS routing using genetic algorithm. The algorithm concentrates on solving the problem of multiple additive QoS parameters, which has been proven to be NP-complete. This paper discusses the various aspects of genetic algorithm design including selection, fitness function, crossover and mutation. The algorithm was implemented and tested on a 55 mesh network to test for its effectiveness. The simulation result shows that this algorithm can perform well regardless of the number of QoS parameters used. 2005 IEEE.